2003
DOI: 10.1128/jvi.77.1.499-510.2003
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Topology of Syncytial Domains of Herpes Simplex Virus Type 1 Glycoprotein K (gK): the UL20 Protein Enables Cell Surface Localization of gK but Not gK-Mediated Cell-to-Cell Fusion

Abstract: Most spontaneously occurring mutations that cause extensive herpes simplex virus type 1 (HSV-1)-induced cell fusion are single amino acid changes within glycoprotein K (gK). Despite the strong genetic association of gK with virus-induced cell fusion, its direct involvement in cellular membrane fusion has been controversial, largely due to previously unsuccessful efforts to detect gK expression on virion and cellular surfaces. Recently, we showed that gK is expressed on HSV-1 virions and functioned in virus ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
118
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(123 citation statements)
references
References 48 publications
4
118
0
1
Order By: Relevance
“…UL20 and gK are involved in secondary envelopment of virions (Baines et al, 1991;Foster & Kousoulas, 1999;Fuchs et al, 1997;Hutchinson & Johnson, 1995;Jayachandra et al, 1997). It has been shown that UL20 is required for the correct trafficking and localization of gK (Foster et al, 2003). In addition, a UL20-null mutation can suppress fusion in the context of infection with a virus carrying a syn mutation in gK or gB (Foster et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…UL20 and gK are involved in secondary envelopment of virions (Baines et al, 1991;Foster & Kousoulas, 1999;Fuchs et al, 1997;Hutchinson & Johnson, 1995;Jayachandra et al, 1997). It has been shown that UL20 is required for the correct trafficking and localization of gK (Foster et al, 2003). In addition, a UL20-null mutation can suppress fusion in the context of infection with a virus carrying a syn mutation in gK or gB (Foster et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular gK Ϫ and UL20 Ϫ HSVs were not obtained in sufficient quantities compared to the other viruses tested in this study. This is due to the critical roles of gK and UL20 in HSV egress (30,(40)(41)(42). However, cell-associated preparations of gK Ϫ and UL20…”
mentioning
confidence: 99%
“…However, our preliminary results have shown that these regulatory T cells are not detectable in the corneas of infected mice (data not shown). Previously, we have shown that the overexpression of gK in gK-transformed cells collapses the Golgi apparatus into the endoplasmic reticulum (10). Thus, the disruption of the Golgi structure by the overexpression of gK in the HSVgK 3 virus may also damage cellular structure of the eye that may result in the exacerbation of CS in infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…This exacerbated CS and facial dermatitis was due to the presence of CD8 ϩ T cells in the cornea of ocularly infected mice (44). Furthermore, we have shown that the overexpression of gK in gK-transformed cells causes a collapse of the Golgi apparatus into the endoplasmic reticulum, which inhibits virion egress, glycoprotein transport, and virus-induced cell fusion (10).…”
mentioning
confidence: 95%